On the thermal properties of expanded perlite – Metallic syntactic foam. (November 2015) - Fiedler, T.; Belova, I.V.; Murch, G.E.
Highlights: Thermal characterisation of novel material. Steady state measurement of thermal conductivity. Correction for thermal contact resistance. Combined experimental, numerical and analytical approach. Abstract: This paper addresses the thermal properties of syntactic metal foam made by embedding expanded perlite particles in A356 aluminium matrix. Lattice Monte Carlo (LMC) analyses are conducted to determine the thermal characterisation of the foam. For increased accuracy, the complex geometry of the metallic foam is captured by micro-computed tomography imaging. Using the resulting detailed geometric models, the effective thermal conductivity tensor is computed with possible thermal anisotropy taken into consideration. The numerical results are verified by comparison with experimental measurements. To this end, an improved steady-state method is used to correct for thermal contact resistance. Furthermore, the effective heat capacity, average density and thermal diffusivity of perlite – metal syntactic foam are determined.